Meaningful Learning of Natural Sciences Based on PBL - Becerra García, Eulalia; Erika Telenchana Perez; Carina Arroba Naranjo; Mora Rosales, José (My University, 2024)
Education requires going beyond educational approaches focused on the transmission and reception of knowledge, through actions that promote meaningful learning. Project-based learning (PBL) is presented as an active methodology to improve the teaching-learning process that allows not only to expand communication skills but also to encourage creativity and awareness for research in students. The objective of this research was to design a guide of didactic activities based on promoting learning through projects from the academic planning, execution and evaluation phases, in order to motivate students through cooperative work and research to solve contextual challenges or problems. Theoretical methods were used: historical analysis, analytical-synthetic, inductive – deductive and techniques such as surveys with questionnaires. This study’s population had 37 seventeen- years- old students from elementary education and 4 teachers from the area of natural sciences. The findings show that teachers face weaknesses related to the use of strategies; therefore, the need to design a guide that promotes PBL activities is necessary. It is evident that students can highly improve with the application of the mentioned guide.
Keywords: Learning; Meaningful; Natural; Projects; Sciences